Формування ідентичності людини під впливом інформаційно-комунікаційних систем - Гальченко, А. І. (ХНУРЕ, 2021)
The author touches upon the issue of human identification in the modern information society. The urgency of the problem of identity for a person in connection with the deepening of informatization of society and the widespread use of information technology is substantiated; The concept of «identity» is understood. The article substantiates that the information society is an unlimited space for self-construction of personality, on the one hand, expanding the space of identification, and, on the other – narrowing the identity itself by choosing ways and forms of self-identification. It emphasizes the importance of communication in the process of acquiring a moral identity in the information society.
Keywords: філософія; формування ідентичності людини